Marvin K. Mooney will you please go now! - Seuss, Dr.; Geisel, Theodor Seuss 1904-. (New York Random House, 1972)
"Suggests in rhyme a number of ways for Marvin K. Mooney to travel as long as he gets going-now!"
Keywords: Stories in rhyme; Fantasy